Flip-flop phenomenon in systemic sclerosis on fluorodeoxyglucose positron emission tomography/computed tomography - DİRESKENELİ, RAFİ HANER; İNANIR, SABAHAT (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Systemic sclerosis (SSc) is a rare autoimmune disease, which may affect multiple organ systems. Fluorine-18-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) can demonstrate the degree and anatomical extent of involvement in the entire body and coexisting malignancies in connective tissue diseases. We present a case of SSc with an increased 18F-FDG uptake in the cutaneous and subcutaneous tissues even higher than the neighboring skeletal muscles (flip-flop phenomenon, that is, an increased 18F-FDG uptake in the skin but a decreased 18F-FDG uptake in the skeletal muscles).
Keywords: Fluorine-18-fluorodeoxyglucose; positron emission tomography/computed tomography; systemic sclerosis